Evaluasi Program Pendidikan dalam Meningkatkan Mutu Pembelajaran di SMP Negeri 51 Surabaya - Nafisah, Lu’luatun; Tukhfah, Aulya Elfarra Naila; Aprilia, Popi; Amalia, Kaniati (TSAQOFAH, 2024)
The purpose of this study was to determine how the evaluation of educational programs in improving the quality of learning at State Junior High School 51 Surabaya. The research method uses a qualitative approach with data collection methods through observation, interviews, and documentation which are then narrated in descriptive form and systematic literature review or known as SLR, which in Indonesian means tinjauan pustaka sistematis namely a method by collecting literature or theories relevant to the article sourced from various references such as books, journals, and other reference sources that discuss related to program evaluation in educational units. The results showed that in improving the quality of learning, State Junior High School 51 Surabaya focuses on character education, literacy and numeracy, and IT-based learning. The evaluation of educational programs is carried out routinely every year based on 6 indicators contained in the education report card, then the process of collecting evaluation data is carried out through AKM activities, then to identify which areas need to be improved based on the results of the evaluation of educational programs, the school uses a priority scale.